2019
DOI: 10.2118/194499-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Mechanisms in Functionalized Multiwalled Carbon Nanotube Flooding for Enhancing the Recovery From Heavy-Oil Reservoirs

Abstract: Summary In the past few years, nanoparticle flooding has displayed significant potential for enhancing oil recovery. Among different nanoparticles, hydrophilic (functionalized) nanotubes have not been tested yet. Therefore, in this study, functionalized multiwalled carbon nanotubes (MWCNT) were used in three concentrations—0.01, 0.05, and 0.1 wt%—to conduct micromodel, interfacial–tension (IFT), wettability, viscosity, phase–behavior, and static–adsorption tests. In addition, constancy of nanofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…An equilibrium exists between the solid–liquid IFT (γ sl ), liquid–gas IFT (γ lg ), and solid–gas IFT (γ sg ), as the water droplet was placed on the rock surface during the contact angle measurement, as indicated in the following equation , γ sg = cos nobreak0em.25em⁡ θ normalc γ lg + γ sl The results of previous studies demonstrated that solid–liquid IFT (γ sl ) plays a prominent role when contact angle measurement is conducted with the sessile drop technique. In addition, the contact angle between the glass surface and liquid droplets is smaller at a higher γ sl value. , Hydrogen bonds could be formed between the surface agents (the surfactant and nanomaterials) and water molecules. The formation of a hydrogen bond increases γ sl ; thus, the contact angle reduces when the NPS solution droplets are placed on rock surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…An equilibrium exists between the solid–liquid IFT (γ sl ), liquid–gas IFT (γ lg ), and solid–gas IFT (γ sg ), as the water droplet was placed on the rock surface during the contact angle measurement, as indicated in the following equation , γ sg = cos nobreak0em.25em⁡ θ normalc γ lg + γ sl The results of previous studies demonstrated that solid–liquid IFT (γ sl ) plays a prominent role when contact angle measurement is conducted with the sessile drop technique. In addition, the contact angle between the glass surface and liquid droplets is smaller at a higher γ sl value. , Hydrogen bonds could be formed between the surface agents (the surfactant and nanomaterials) and water molecules. The formation of a hydrogen bond increases γ sl ; thus, the contact angle reduces when the NPS solution droplets are placed on rock surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Ghalamizade et al detected the EOR potential of hydrophilic multiwalled carbon nanotubes. Visual micromodel tests disclosed that nanoparticles increased the sweep efficiency and reduced the viscous fingering phenomenon.…”
Section: Nanofluid Flooding Eor Techniquesmentioning
confidence: 99%
“…Then, smart water was injected into the micromodel at a rate of 0.05 mL/h. It should be noted that this flow rate was chosen to avoid turbulence behavior in the micromodel (Ghalamizade Elyaderani et al 2019). Next, the picture of micromodel was taken by a camera at constant time intervals to measure the oil recovery factor.…”
Section: Flooding Testsmentioning
confidence: 99%